Factors Affecting The Level of Knowledge of Postpartum Mothers About Perineal Wound Care at The Independent Practice of Midwife E, Kalijati District, Subang Regency, 2025 - Mela Sari; Hani Septiani; Dini Ariani; Sri Heryani (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2025)
Introduction: The postpartum period is a critical phase during which mothers undergo significant physiological and psychological changes that may increase their vulnerability to complications such as perineal wound infections. Perineal injuries remain one of the leading causes of postpartum infection, particularly in developing countries where access to health information and quality midwifery care is limited. Adequate maternal knowledge regarding perineal wound care is essential in preventing infection, promoting healing, and reducing morbidity. However, many postpartum mothers still lack proper understanding of wound care practices due to factors such as limited education, inadequate information sources, and insufficient counseling from healthcare providers. Objective: This study aimed to identify the factors influencing the level of knowledge of postpartum mothers regarding perineal wound care at the Independent Practice of Midwife E, Kalijati District, Subang Regency, in 2025. Method: A descriptive-analytic approach with a cross-sectional design was employed. A total of 35 respondents were selected using accidental sampling, and data were collected through structured, validated, and reliable questionnaires. Univariate analysis was conducted to describe respondent characteristics, while bivariate analysis using the Chi-Square test examined correlations between variables. Result: The results showed that most respondents were greater than or equal to 25 years old, had intermediate education, were housewives, were multiparous, and primarily received information from healthcare workers. The majority had a fair level of knowledge (48.6%). Significant relationships were found between education level (p = 0.016) and information source (p = 0.027) with knowledge level, while age, occupation, and parity showed no significant associations. Conclusion: In conclusion, education and information sources are key determinants of postpartum mothers knowledge of perineal wound care. Strengthening health education by midwives is essential to enhance maternal understanding, prevent infection, and support optimal postpartum recovery.